Improving Student Learning Outcomes in Fiqh Learning by Applying the Team Games Tournament Model at MIS DDI Gattungan - Nurpadilah; Irfan (MANDAILING GLOBAL EDUKASIA, 2024)
This classroom action research aims to improve student learning outcomes in Fiqh learning by applying the Team Games Tournament (TGT) model at MIS DDI Gattungan. The background of this study stems from the low achievement and lack of enthusiasm of students in Fiqh subjects, which are often delivered through monotonous and teacher-centered methods. The TGT model, which integrates cooperative learning with competitive elements, is expected to foster active participation, collaboration, and deeper understanding among students. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were fifth-grade students of MIS DDI Gattungan, totaling 24 participants. Data collection techniques included observation, tests, and documentation, while data analysis was carried out using both qualitative and quantitative descriptive methods. The results show a significant improvement in student learning outcomes after the implementation of the TGT model. In the first cycle, the average class score increased from the initial 58.7 to 71.2, with 62.5% of students reaching the minimum completeness criteria (MCC). In the second cycle, the average score rose further to 83.4, with 91.7% of students meeting the MCC. Additionally, students demonstrated higher levels of motivation, collaboration, and engagement during learning activities. These findings indicate that the TGT model is effective in enhancing both cognitive and affective aspects of student learning in Fiqh. Therefore, this model is recommended as an alternative approach to improve the quality of Islamic education in elementary schools. Future research may focus on applying this model to other Islamic subjects and different student populations.